Sekolah dari Lereng Pegunungan: Diversifikasi Layanan Pendidikan Nonformal Berbasis Musholla di Kampung 17, Batu Lawang, Cianjur - Vemmi Kesuma Dewi, Raden Roro; Rahmianti, Siti; Lituhayu, Asri Andriana (Khidmatussifa: Journal of Islamic Studies, 2025)
Abstract: Kampung 17, a remote highland village in Batu Lawang, Cianjur, presents a challenging educational landscape. Isolated by valleys and steep ravines, children face severe difficulties accessing formal schools, which are located far and are hard to reach. The community’s low socioeconomic status, combined with limited electricity and infrastructure, exacerbates these constraints. This phenomenon underscores the urgent need for diversified nonformal education services that can reach and empower children in this area. This study examines the implementation of a nonformal education model based at Musholla Baitul Muttaqien as a "Musholla Literacy House," adopting the concepts of a Borderless School and Project-Based Learning. Using a qualitative case study approach, this research highlights how the musholla serves not only as a place of worship but also as an innovative and inclusive learning center that integrates literacy activities, life skills, and local cultural preservation. The findings are expected to contribute significantly to the development of adaptive and sustainable alternative education services for remote communities. Thus, education ceases to be a distant dream on the mountain slopes, becoming a tangible and accessible hope. Keywords: Education Diversification, Nonformal Education, Musholla Literacy House, Borderless School, Project-Based Learning, Remote Village, Batu Lawang, Cianjur